Effect of rim and web interaction on crack propagation paths in gears by means of XFEM technique. Issue 10 (13th April 2015) - Curà, F.; Mura, A.; Rosso, C.
Abstract The objective of this work is to investigate the correlation between rim and web thickness on the crack propagation path in thin‐rimmed gears, referring to bending failures. To this aim, numerical simulations have been performed, based on the 3D extended finite element method. Results related to gear models with different web and rim thickness have been interpreted in ISO Standard environment, relating the crack path to the so called gear blank factor CR, useful in cases of mating gears consisting of rims and webs. Results show that the interaction between web and rim thickness may influence the crack propagation and the corresponding safe or catastrophic failure mode.